1998
DOI: 10.1136/fn.78.1.f38
|View full text |Cite
|
Sign up to set email alerts
|

Does positive pressure ventilation increase arginine vasopressin in preterm neonates?

Abstract: Aim-To examine the eVect of intermittent positive pressure ventilation (IPPV) on plasma arginine vasopressin concentration (pAVP) in preterm neonates. Methods-Thirty five neonates were classified, at the time of blood sampling, into three groups: unstable ventilated; stable ventilated; and stable non-ventilated. A modification of an extraction method for pAVP was developed for use in studies on very small babies, and sampling methods were compared. Results -The pAVP (median, range) was similar in the ventilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Lambert et al [22] reported similar plasma vasopressin levels in ventilated preterm neonates to those in the present study and demonstrated an inverse relationship between systolic blood pressure and plasma AVP concentration. It is demonstrated that the most dominant stimulus for secretion of vasopressin is high serum osmolarity in animal studies [26,27] .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Lambert et al [22] reported similar plasma vasopressin levels in ventilated preterm neonates to those in the present study and demonstrated an inverse relationship between systolic blood pressure and plasma AVP concentration. It is demonstrated that the most dominant stimulus for secretion of vasopressin is high serum osmolarity in animal studies [26,27] .…”
Section: Discussionsupporting
confidence: 73%
“…ported to have fluctuations in serum cortisol and AVP concentrations [20][21][22] . On the other hand, preterm infants before 27 weeks are reported to have lower serum cortisol levels compared to adults [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In one series [17], comparison of results from three groups of preterm infants demonstrated that those with RDS were unable to excrete the administered fluid, gained weight and developed hyponatraemia. In animal models positive pressure ventilation is also a stimulus for AVP release [18], but the effect of ventilation on AVP levels in the human is debated [3,11,[19][20][21]. In one study [3] continuous sequential urinary arginine vasopressin measurement in 14 preterm ventilated infants demonstrated that AVP levels increased during deterioration of the respiratory illness, mask ventilation and the development of bilateral pneumothoraces or severe intraventricular haemorrhage [3].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] SIADH may be caused by various conditions, such as disorders involving the central nervous system, a variety of malignant tumors, major abdominal or thoracic surgeries, symptomatic HIV infection, and intrathoratic disorders such as infections, positive pressure ventilation, and conditions with a decrease in left atrial pressure. [ 2 ] Also, a large number of drugs have been shown to cause SIADH including chlorpropamide, carbamazepine, oxcarbazepine, SSRIs, and a number of cytotoxic drugs such as vincristine, vinblastine, cisplatin, cyclophosphamide, and melphalan. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%